2015
DOI: 10.1002/jctb.4734
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazinolyzed cellulose-g-polymethyl acrylate as adsorbent for efficient removal of Cu(II) and Ni(II) ions from aqueous solution

Abstract: BACKGROUND: Although methyl acrylate has been graft polymerized from cellulose and functionalized with hydrazine and hydroxylamine for removal of copper and nickel ions, the adsorption capacity was less than 80 mg g −1 . The present work reported hydrazinolysis of cellulose-graft-polymethyl acrylate and remarkably improved adsorption capacity for Cu(II) and Ni(II) in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…On a closer look at Table 7, both Godiya et al 29 and Huang et al 32 reported higher amount of adsorption of Cd(II) compared to our work. Similarly, Jia et al 22 reported a higher amount of adsorption of Ni(II) compared to our work. All three of them used the lowermolecular-weight-based repeat units such as acrylamide, acrylic acid, and methyl acrylate, respectively, which provide more number of binding sites than the same weight of polysaccharide-based hydrogels.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…On a closer look at Table 7, both Godiya et al 29 and Huang et al 32 reported higher amount of adsorption of Cd(II) compared to our work. Similarly, Jia et al 22 reported a higher amount of adsorption of Ni(II) compared to our work. All three of them used the lowermolecular-weight-based repeat units such as acrylamide, acrylic acid, and methyl acrylate, respectively, which provide more number of binding sites than the same weight of polysaccharide-based hydrogels.…”
Section: Methodssupporting
confidence: 78%
“…Adsorption behavior depends on various parameters such as ionic concentration, pH, contact time, temperature, etc. In recent years, acrylate-, acrylamide-, alginate-, poly­(vinyl alcohol)-, and chitosan-based hydrogels are used to remove Ni­(II) and Cd­(II) from wastewater. Cellulose-based hydrogels are widely used for wastewater treatment .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the negative value of Δ S ° suggests that decreased randomness at the solid–liquid interface during adsorption of Fe 3+ ions onto CMC‐g‐AMPS hydrogel. The result is similar to previous studies . In addition, the negative value of Δ S ° also reflects the poor affinity of Fe 3+ ion towards CMC‐g‐AMPS hydrogel .…”
Section: Resultssupporting
confidence: 91%
“…The result is similar to previous studies. 46,[55][56][57] In addition, the negative value of ΔS ∘ also reflects the poor affinity of Fe 3+ ion towards CMC-g-AMPS hydrogel. 56 This result supported that the lowest equilibrium capacity of CMC-g-AMPS for Fe 3+ ion when compared with Cu 2+ and Pb 2+ ions.…”
Section: Effect Of Contact Time and Temperature On Heavy Metal Ions Fmentioning
confidence: 99%
“…Table displays the adsorptive removal of Cu­(II) onto the Zr-MOFs enhanced by cross-flow disturbance of ceramic membrane as compared to other different adsorbents and methods in terms of adsorption capacities under certain conditions. From these data, it can be seen that the adsorption capacity of the method proposed by this study is significantly higher than the other cases that were previously reported. ,, In the other words, Zr-MOFs enhanced by cross-flow disturbance of ceramic membrane have great potential ability for significantly high removal of Cu­(II) from heavy metal wastewater.…”
Section: Resultsmentioning
confidence: 50%